Built‐in ESD Protection for RFID Tag ICs. Issue 6 (1st November 2016) - Ding, Yi; Hu, Jianguo; Duan, Zhikui; Wang, Deming; Ding, Yanyu; Tan, Hongzhou
Abstract : The built‐in Electro‐Static discharge (ESD) protection circuits for Radio frequency identification (RFID) tag ICs are proposed. The ESD protection function is built into the rectifier and amplitude limiter. The rectifier and limiter are connected directly to the RF interface, and some transistors can discharge the larger current. These transistors can be used to build ESD protection circuits, through the redesign and optimization. The built‐in ESD protection circuits can improve the ESD protection level and reduce the layout area. The circuits have been fabricated in 0.18μm CMOS process. The test results show that the built‐in ESD protection circuits work well under 4kV ESD pressure and save as much as 72% of the layout area compare with foundry standard ESD protection cells.